Rahn (Gadai) Dalam Perspektif Tafsir Dan Hadits Serta Implementasinya Pada Lembaga Pegadaian Syariah - Sumiati Sumiati; Ahmad Damiri; Ending Solehudin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
The writing of this article is based on the idea that Sharia economic law is part of the Islamic legal system which originates from the Koran and al-hadith. The purpose of this study is to find out the opinion of scholars about the interpretation of QS. Al-Baqarah paragraph 283, and to find out the suitability of the interpretation of QS. Al-baqarah verse 283 with the Rahn concept in the Sharia Pawnshop Institution. The type of research used is library research. The results of this study stated 1). Rahn is making an item that has an asset value in the view of syara' as collateral for a debt, which makes it possible to take all or part of the debt from the item, this is also in line with Article 1150 of the Civil Code. Textually Rahn is contained in the Al-Qur'an Surah Al-Baqarah Verse 283, in this verse some of the salaf scholars say that the pawning law is not enforced except when traveling, but in general the scholars are of the opinion that the content of this verse does not require that collateral is only permissible on trips, muamalah transactions not in cash, and also there is no one who is used as a writer. However, basically this paragraph only requires that in such conditions muamalah activities may be carried out by providing a guarantee. 2). The practice of pawning at Islamic pawnshops refers to the Fatwa of the National Sharia Council number: 25/DSN-MUI/III/2002 dated June 26 2002 concerning rahn and is declared to have conformity with Sharia principles, as well as technically refers to OJK Regulation Number 31/Pojk.05 /2016 Concerning Pawn Business.